THE TRANSFORMATION FROM SOCIOPRENEURSHIP TO SUFIPRENEURSHIP: A CONCEPTUAL FRAMEWORK FOR SPIRITUALIZING THE ENTREPRENEURIAL SPHERE IN CONTEMPORARY ISLAM - Budi Rahman Hakim (Adisam Publisher, 2026)
This study aims to formulate and develop a new conceptual framework called sufipreneurship, as a response to the spiritual void within contemporary Islamic entrepreneurship models. By integrating a conceptual-philosophical approach and Sufi hermeneutics, sufipreneurship offers an entrepreneurial paradigm that incorporates core Sufi values—ikhlas (sincerity), zuhud (asceticism), tawakkul (trust in God), khidmah (service), and muraqabah (divine awareness)—into business practices that are spiritual, social, and ethical in nature. This concept not only expands the epistemology of Islamic entrepreneurship but also provides a normative critique of the secular capitalist model, which desacralizes the meaning of work and reduces it to mere profit maximization. The study employs a literature-based research method combined with data triangulation from classical and contemporary sources, along with field observations from Sufi communities (ṭarīqa). The findings suggest that sufipreneurship presents a relevant and practical alternative for addressing the ethical and spiritual crises within the Muslim business world. The implications of this research include the development of a Sufi-based entrepreneurship curriculum, policy recommendations for spiritually grounded Islamic economic empowerment programs, and strategic collaborations between religious institutions (ṭarīqa) and Islamic economic sectors. Hence, sufipreneurship offers a business framework that is maṣlaḥah-oriented, sustainable, and deeply rooted in Islamic spirituality.